(untitled) (Bangladesh Journal of Agriculture, 2024)
Aromatic rice has tremendous economic and social value, but commercial production in Bangladesh is limited due to lower yields. In this study, the heterosis of hybrid rice was exploited to improve the yield of aromatic rice. A total of 120 aromatic rice germplasm was tested against five cytoplasmic male sterility (CMS) lines (A) with 40 maintainer (B) and 11 restorer (R) lines and the B lines were converted into CMS lines using backcrossing. The identified 11 restorer lines were being maintained, four local R-lines (Sakkorkhora, Chinigura, Kataribhog and BAU dhan2) were used by assessing pollen and spikelet fertility of the F1 generation from crosses of 50 selected R-lines against one CMS line (IR58025A). Quasi-hybrid-1 has a yield potential >5.0 t/ha. Growth duration varied in-between 85-90 days during the transplanted Aman season, and there was heightened zinc content (>22 mg/kg) in the hybrid grains. Identified restorer and maintainer local genotypes provide broad resources for increasing aromatic rice yield and could help meet the demand for aromatic rice in domestic and international markets. Bangladesh J. Agri. 2024, 49(1): 19-32